Myxobolus taibaiensis sp. n. (Myxozoa: Myxosporea) infecting the intestinal wall of common carp Cyprinus carpio Linnaeus in China - Liu, Xinhua; Hua, Congjie; Zhang, Qianqian; Zhao, Yuanli; Zhang, Dong; Zhang, Jinyong (Folia parasitologica, 2017)
Myxobolus taibaiensis sp. n. was found in the inner intestinal wall of common carp, Cyprinus carpio Linnaeus, during the investigation of fish parasite fauna in Lake Taibai, located in the middle reach of the Yangtze River, China. The whitish ellipsoidal plasmodia, up to 2.9 mm long and 1.7 mm wide, developed in the circular muscle layer of the intestinal wall and produced significant compression into adjacent tissues, but no significant inflammatory responses were observed against this infection. Mature spores are oval in frontal view and lemon-like in lateral and apical view, averaging 10.2-11.2 µm (10.8 ± 0.2 µm) in length, 9.1-9.9 µm (9.6 ± 0.2 µm) in width and 6.1-6.6 µm (6.3 ± 0.1 µm) in thickness. Polar capsules are pyriform, equal in size, slightly converging anteriorly, measuring 4.4-5.4 µm (5.0 ± 0.2 µm) in length by 3.2-3.6 µm (3.4 ± 0.1 µm) in width. Polar filaments coiled with four to five turns and arranged perpendicular to the polar capsule length, measuring up to 106 µm. Myxobolus taibaiensis sp. n. is morphologically similar to Myxobolus rotundatus Achmerov, 1956 which also infects the inner wall of the intestine of common carp. However, the small subunit ribosomal DNA sequence identity was only 94%, generally beyond the intraspecies variation in the genus. Phylogenetically, this new species is sister to M. rotundatus and then clusters with M. shantungensis Hu, 1965 to form an independent common carp-infecting cluster within the Henneguya-Myxobolus clade.
Keywords: Animals; Intestines; spory; Myxobolus; Spores; China; jezera; kapři; nemoci ryb; Fish Diseases; Parasitic Diseases, Animal; Phylogeny; střeva; parazitární nemoci u zvířat; Čína; Carps; Lakes; zvířata; fylogeneze